Comparative Analysis of Second - Tier Patent Protections and Their Impact on SME Innovation: A Cross – Jurisdictional Study of Germany, The United Kingdom, And Australia - Jayawardana, Y.P.N.; Peiris, K.P.S.G. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
This article presents a comparative legal analysis of second-tier patent protection (STP) regimes and their implications for small and medium-sized enterprises (SMEs) in Germany, the UK, and Australia. SMEs are considered to be crucial enablers of incremental innovation, but they often have to cope with structural as well as higher cost obstacles when it comes to interacting with traditional patent systems. In light of these problems, several jurisdictions have implemented new types of STPs such as utility models, innovation patents and supplementary protection certificates (SPCs) intended to provide faster, cheaper and easier forms of protection. But not all of these tools are equally effective in legal or policy terms. Germany’s utility model (Gebrauchsmuster) shows that STPs can be embedded in broader industrial and innovation policy, offering SMEs easily accessible protection despite doubts on enforceability and patent quality. By contrast, Australia’s innovation patent system, intended to assist SMEs, has been subject to strategic filing and low-quality grants and was repealed in 2021. The UK does not have a general STP system, favouring patent quality and sectoral instruments like SPCs that are not SME focused. By the use of doctrinal, policy and empirical analysis, this study establishes the trade-offs in terms of accessibility, quality and policy coherence. It finds that the presence of STPs alone is not enough for stimulating innovation amongst SMEs and this effectiveness relies crucially on STPs’ design elements, their linkage with institutional protection mechanisms, and coherence with national innovation strategy. For developing countries, including Sri Lanka, they highlight the need for locally sensitive law and policy reforms rather than mindless borrowing. This comparative framework provides some useful lessons to policy makers in search of compromising innovation incentives, patent quality and SME access along different legal systems.
Keywords: Second-tier patents (STP); SME; Innovation; Utility models; Supplementary protection certificates; Intellectual property law; Incremental innovation